Effect of Cycloplegia on Keratometric and Biometric Parameters in Keratoconus. (12th December 2016) - Polat, Nihat; Gunduz, Abuzer
Abstract : Purpose. To obtain information about effect of cycloplegia on keratometry and biometry in keratoconus. Methods. 48 keratoconus (Group 1) and 52 healthy subjects (Group 2) were included in the study. We measured the flat meridian of the anterior corneal surface (K1), steep meridian of the anterior corneal surface (K2), lens thickness (LT), anterior chamber depth (ACD), and axial length (AL) using the Lenstar LS 900 before and after cycloplegia. Results. The median K1 in Group 1 was 45.64 D before and 45.42 D after cycloplegia, and the difference was statistically significant (P < 0.05 ). The median K2 in Group 1 was 50.96 D before and 50.17 D after cycloplegia, and the difference was significant (P < 0.05 ). The median K1 and K2 in Group 2 were 42.84 and 44.49 D, respectively, before cycloplegia, and 42.84 and 44.56 D after cycloplegia, and the differences were not statistically significant (allP > 0.05 ). There were significant differences in SE, LT, ACD, and RLP between before and after cycloplegia in either Group 1 (allP < 0.05 ) or Group 2 (allP < 0.05 ). There were not statistically significant differences in AL between before cycloplegia and after cycloplegia in either Group 1 (P = 0.533 ) or group 2 (P = 0.529 ). Conclusions. Flattened corneal curvature and increase in ACD following cycloplegia in keratoconus patients were detected.